Model Optimalisasi Pajak Sumber Daya Alam Di Berbagai Negara Berkembang: Systematic Literature Review - Suryati, Tri Frida (LPPM POLITEKNIK LP3I BANDUNG, 2025)
Developing countries are endowed with abundant natural resources; however, this wealth is often not reflected in national revenue due to weak taxation system. Natural resource taxation is expected to contribute significantly to fiscal sustainability while ensuring fair and efficient resource exploitation. Nonetheless, challenges such as weak regulation, low tax compliance, limited administrative capacity, and information asymmetry hider revenue optimization . This study conducts a Systematic Literature Review (SLR) guided by the PRISMA methodology to synthesize findings from 20 selected articles. It identifies gaps and recurring patterns in previous research and formulates a conceptual model for natural resources tax optimization in developing contexts. The model integrates economic, institutional, and governance dimensions while emphasizing evidence-based policy making. The findings offer both theoretical contributions to public sector accounting and practical insights for policymakers in designing sustainable and equitable fiscal policies for resources-rich developing countries.